Utilizing The iNaturalist Application for Biology Research and Learning - Ipin; Aden Arif Gaffar; Rika Firda Rizkia; Diana Yulianti (Mangifera Edu, 2023)
This literature study aims to describe the utilization of the iNaturalist application (https://www.inaturalist.org/) in biology research and learning activities. iNaturalist is an Online Citizen Science (OCS) application available on the web and Android (Apps) platforms. This application has various features for collecting, identifying, and mapping varied biodiversity worldwide. It is suitable for biodiversity research and can also be used in learning biology on relevant concepts such as biodiversity, ecology, environment, plantae, animalia, and others. This article will discuss the advantages of the iNaturalist application, how to use it, and the utilization of the application in learning biology. The working principle of the iNaturalist application is to utilize artificial intelligence technology in the form of image processing so that it can identify various uploaded biodiversity data. This application offers community learning, the process of identifying research data involving the iNaturalist community worldwide. The way the iNaturalist application works is that users record data, share data with fellow naturalists and discuss research results. iNaturalist in research can be used for collecting, identifying, and publishing ecological, environmental, and biodiversity research data. The use of iNaturalist application in learning can be used in biology learning to train science process skills, especially observation skills, biodiversity learning, taxonomy learning, and research skills. In addition, this application supports Citizen Science activities that are suitable for use in education biology because it can create contextual and collaborative learning.